Social vulnerability and Lyme disease incidence: a regional analysis of the United States, 2000-2014 - Dhitinut Ratnapradipa; Justin Tyler McDaniel; Alexandra Barger (Epidemiology, Biostatistics and Public Health)
Background: Lyme disease (LD), which is highly preventable communicable illness, is the most commonly reported vector borne disease in the USA. The Social Vulnerability Index (SoVI) is a county level measure of SES and vulnerability to environmental hazards or disease outbreaks, but has not yet been used in the study of LD. The purpose of this study was to determine if a relationship existed between the SoVI and LD incidence at the national level and regional division level in the United States between 2000 and 2014.